TRADISI SEDEKAH BUMI SEBAGAI MEKANISME INTEGRASI SOSIAL: STUDI KERUKUNAN UMAT BERAGAMA DI KEDIRI - M. Thoriqul Huda (Institut Agama Islam Ngawi, 2025)
This study examines the Sedekah Bumi tradition in Kediri as a cultural practice that extends beyond an agrarian thanksgiving ritual and functions as a social mechanism that shapes, tests, and reproduces interreligious tolerance. Using a descriptive qualitative approach supported by structural functionalism and symbolic interactionism, this research reveals that relations among Muslim, Christian, and Catholic communities are constructed not merely through theological understanding but through everyday social practices that regulate patterns of interaction, role distribution, and the creation of shared meaning. The Sedekah Bumi tradition serves as a space for identity negotiation, enabling equal interaction through ritual participation, communal cooperation, and village deliberation, ultimately fostering a form of pragmatic rather than normative tolerance rooted in collective experience. Analytically, the tradition fulfills all four components of Talcott Parsons’ AGIL framework: adaptation to religious plurality and social change, goal attainment through shared agreement on rituals, integration through cross-faith interactions, and latency through the transmission of communal values such as cooperation and solidarity. The findings highlight that local wisdom operates as a dynamic form of social capital that strengthens the resilience of multireligious communities and serves as a crucial pillar in maintaining social harmony and stability amid potential identity fragmentation in contemporary society. Keywords: Sedekah Bumi, Practical Tolerance, Structural Fungcional.